(3eaGJjM GdCUhds - (3GdWHGWHGFj GdcQHdGFj, GdeLGgO, eMeO Hf Ydj Hf eMeO Hf Ydj, J (B1242 (3g`s
(3ChdgG (B:s
(3HGH GdCaYGd hGdJCSj ; (B... (3GYde Cf aYd GdfHj Udi Gddg Ydjg hSde (B.. (3aEf cGf HjGfG deLed hGLH dfG cGf Ydi GdhLhH aj MbfG Ch GdefOhH cPcdc cGf aj MbfG (B...s
(3BNQgG (B:s
... (3hdcf GdCbQH YfOj JQLjM GdGSJUMGH GdPj jYGVOg HeG jajOg GdXf cTgQI hGSJbQGA hfMhgeG YOG GdbjGS hgd jJe ML CMOgeG Ydi GdBNQ HGYJbGOg HeKdg ef Odjd (B... (3bO aQZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\543s
(3EjVGM Gdecfhf (B2\520s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs